Zastrzeżenia do decyzji Komisji Europejskiej z 28 października 2016 roku w sprawie zmiany zwolnienia dla gazociągu OPAL (sprawa C(2016)6950 final) - Zajdler, Robert (Polityka i Społeczeństwo, 2020)
The investment process in gas infrastructure is often burdened with high investment costs and the risks associated with ensuring its viability. In order to achieve the public objective of security and stability of supply and competition in the natural gas market, while limiting the investment risk on the investor side of the new gas infrastructure, regulations have been introduced to allow the investor not to apply the legal requirements set out in Article 22 of Directive 2003/55/EC (amended by Article 36 of Directive 2009/73/EC) for a specified period of time and after fulfilment of the indicated requirements. The exemption granted by the European Commission to the OPAL gas pipeline by the decision of 28 October 2016 raises doubts as to the legal basis of such exemption and the fulfilment of the substantive conditions governing its granting. The article analyses the decision by criticizing the grounds and merits of its adoption.